2014
DOI: 10.1248/bpb.b14-00576
|View full text |Cite
|
Sign up to set email alerts
|

Renin Inhibition Improves Ovariectomy-Induced Osteoporosis of Lumbar Vertebra in Mice

Abstract: The skeletal renin-angiotensin system (RAS) is involved in the progression of osteoporosis and the active peptide within the RAS, angiotensin II (ANG II), has deleterious effects on bones. This study was performed to investigate whether suppression of the rate-limiting step of the RAS cascade by the renin inhibitor aliskiren has a benefit on trabecular bone in osteoporotic mice. A postmenopausal osteoporosis model was induced by bilateral ovariectomy. The ovariectomized (OVX) mice were treated with a low (5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…This chronic ulcer model, which highly resembles human chronic ulcers in terms of pathological features and healing mechanisms, is utilized to develop novel anti-ulcer medication, which may potentially prevent ulcer relapse or enhance ulcer healing (26). Acetic acid is reported to produce ulcers by gastric obstruction leading to increased quantities of acidic gastric juice (27,28). In the current study, arctigenin caused significant reductions in gastric lesions at all doses tested, when compared with the vehicle group (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…This chronic ulcer model, which highly resembles human chronic ulcers in terms of pathological features and healing mechanisms, is utilized to develop novel anti-ulcer medication, which may potentially prevent ulcer relapse or enhance ulcer healing (26). Acetic acid is reported to produce ulcers by gastric obstruction leading to increased quantities of acidic gastric juice (27,28). In the current study, arctigenin caused significant reductions in gastric lesions at all doses tested, when compared with the vehicle group (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…The first among these treatments was the angiotensin-converting enzyme inhibitors (ACEIs), followed by the ANG II receptor blockers (ARBs), while the major problem associated with the application of these drugs is the compensatory rise of renin due to the disruption of the feedback inhibition of renin production (Zhang et al 2008). Additionally, given the contradictory results about the effects of RAS inhibitors including ACEIs and ARBs on skeletal system in previous animal and clinical studies (Kwok et al 2012;Zhang YF et al 2012;Yang et al 2016), and renin inhibitor aliskiren consistently exerted protection from bone loss of osteoporotic animals (Zhang FY et al 2014;Zhang Y et al 2016aZhang Y et al , 2016b, it might be a challenge in exploring bioactive ingredient targeting renin activity. Since renin is the rate-limiting enzyme of the RAS (Zhang Y et al 2016a(Zhang Y et al , 2016b, tremendous research efforts have been performed to identify active renin inhibitors and some drug candidates have entered into clinical trials (Sun et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies showed that the increased activity of skeletal RAS, especially the over-activation of the renin/ANG II/AT1R signalling at high glucose state, was detrimental to bone tissue (Zhang Y et al , 2016a(Zhang Y et al , 2016bLi et al 2015;Yamamoto et al 2015). Since renin is the rate-limiting enzyme of the RAS cascade (Zhang Y et al 2012), the renin inhibitor like aliskiren exerted beneficial effects on skeletal system in animal studies (Zhang FY et al 2014;Zhang Y et al 2016aZhang Y et al , 2016b. While the therapeutic reagents derived from natural products and traditional herbs acting on the renin/ANG II/AT1R pathway are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Zhang et al (39) reported that vitamin D was able to inhibit RAS activity in the kidney, improve renal function and prevent the occurrence of nephritis and fibrosis in mice caused by long-term hyperglycemia or unilateral ureteral obstruction. In the present study, 1,25(OH) 2 D 3 treatment improved the quality of cancellous bone in GIOP mice by inhibiting local RAS activity in bone tissue through a reduction in the generation of Ang II, thus downregulating the expression of osteoclast factors that may reduce bone resorption activity.…”
Section: Discussionmentioning
confidence: 99%